Utilizing functional lumen imaging probe topography to evaluate esophageal contractility during volumetric distention: a pilot study. Issue 7 (20th April 2015) - Carlson, D. A.; Lin, Z.; Rogers, M. C.; Lin, C. Y.; Kahrilas, P. J.; Pandolfino, J. E.
Abstract Background The functional lumen imaging probe (FLIP) measures luminal cross‐sectional area and pressure during volumetric distension. By applying novel customized software to produce FLIP topography plots, organized esophageal contractility can be visualized and analyzed. We aimed to describe the stimulus thresholds and contractile characteristics for distension‐induced esophageal body contractility using FLIP topography in normal controls. Methods Ten healthy controls were evaluated during endoscopy with FLIP. During stepwise bag distension, simultaneous intra‐bag pressure and luminal diameter measurements were obtained and exported to a MatLab program to generate FLIP topography plots. The distension volume, intra‐bag pressure, and maximum esophageal body diameters were measured for the onset and cessation of repetitive antegrade contractions (RACs). Contraction duration, interval, magnitude, and velocity were measured at 8 and 3‐cm proximal to the esophagogastric junction. Key Results Eight of ten subjects demonstrated RACs at a median onset volume of 29 mL (IQR: 25–38.8), median intra‐bag pressure of 10.7 mmHg (IQR: 8.6–15.9), and median maximum esophageal body diameter of 18.5 mm (IQR: 17.5–19.6). Cessation of RACs occurred prior to completion of the distension protocol in three of the eight subjects exhibiting RACs. Values of the RAC‐associated contractile metrics were also generated to characterize these events. Conclusions & Inferences Distension‐induced esophageal contractions can be assessed utilizing FLIP topography. RACs are a common finding in asymptomatic controls in response to volume distention and have similar characteristics to secondary peristalsis and repetitive rapid swallows.